The Role of Social Science to Build Social Awareness Among Elementary School Students - Marsini, M. (Golden Ratio of Mapping Idea and Literature Format, 2025)
This study aimed to explore how social science learning in elementary schools could play a role in building children's social intelligence. By conducting a qualitative approach and literature review, this study examined various concepts, theories, and practices in social science learning that could improve students' social skills. Data was collected by reviewing articles, journals, and relevant books discussing the relationship between social education and children's social intelligence development. The study results indicated that theoretically, social science materials focused on social values, culture, and interactions between individuals in society, and students could gain a deep understanding of the importance of empathy, tolerance, and cooperation in social life. In addition, social science learning could also provide direct experiences that enable students to apply social concepts in their daily lives. This study recommended that the social science curriculum in elementary schools should more fully integrate an approach based on the development of social intelligence to shape students' characters until they are prepared to face future social challenges.